The introductive experience of Half-Way Houses - Quantitative and qualitative analysis - Jaqueline Q. de Macedo; Maria de F. de A. Silveira (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Due to Psychiatric Reform, the attention in mental health has changed the paradigm and models of assistance, like the appearing of the Half-way House Service. This service has the objective of offering a new kind of attention to the ex-hospitalized who don't have the family's support anymore, to return to the community and who come from long-term psychiatric institutionalization.  This research's objectives are the knowing and understanding the resident's perception about the Assisted Living Facilities, catching up on information about their clinical conditions and describing their daily lives. It's a transversal, descriptive and exploratory research with an quantitative and qualitative approach. The data collection was done by semi-structured interviews. The results showed the existence of six Assisted Living Facilities in Campina Grande, with 45 residents, being 56% men, 31% aged between 40-49 years old, and and average of institutionalization (63%) of 21 to 30 times, being 33% between 11 a 20 years old. Through the speeches a search for the autonomy is perceived, pointing towards two categories: Taking care of yourself and Participation in housework, according to the possibilities of each dweller. However, the lack of will to do activities, a characteristic in the asylum institutions is still updated. So, the quality of life provided by this service has in the reconstruction of the social interactions, its greatest therapy, complex and in construction, because it's recent, reasoned in paradigm of psychosocial rehabilitation and important for the social reinsertion of the previously institutionalized patients.